Fenomenologi Keluarga Korban Bencana Gempa Pidie Jaya di Kota Meureudu - Al KAUTSAR (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
AbstractMeureudu has faced disasters thrice in past of eight years. In 2009, flood occured in Pidie, in 2013 there was a wildfire, and in december 2016, there was an earthquakes which affected the people in Meureudu. There were a lot of families in Meureudu getting harm in big amount. In seeking a disaster,Koss (1946), developed a model which is named as ‘roller coaster’ and afterwards developed by Hill (1949). The model of Roller Coaster is used to find out the social process happened in family during the disaster period. Based on Roller Coaster mode, there are some phases happened in family during the disaster period. This research used qualitative phnomenology. The phenomenology research is used to obtain the data from the experience which happened to the subject of the phenomena. That experience afterwards describe the condition of the subject who is investigated on that phenomena. The disasters occured bring some impacts to the family who as victims of the disasters in Meureudu. The impact can probably affect each family differently.Key words: Family, Disaster, Phenomenology, Meureudu City